Meat quality and fatty acid profile in broilers as affected by low-fat Tenebrio molitor meal in the diet - Popova, Teodora; Petkov, Evgeni; Vlahova-Vangelova, Desislava; Kolev, Nikolay; Balev, Desislav; Dragoev, Stefan; Dimov, Krasimir (Frontiers in Animal Science, 2025)
The study aimed to investigate the effect of the inclusion of low-fat Tenebrio molitor meal (LFTM) as partial replacement of soybean in the diet of broilers on the physical properties, chemical composition and fatty acid profile of the meat. The trial included a total of 120 male one-day-old Ross 308 broilers allocated to 5 groups. After 14 days of adaptation, the birds were fed a basal diet (C) and diets including LFTM in amounts of 2.5% (T2.5), 5% (T5), 7.5% (T7.5), and 10% (T10). At 35 days of age, 8 birds per group were sacrificed and subjected to analysis of the meat quality. The higher dietary levels of LFTM were associated with decrease in pH24 (linear, P<0.0001), but increased L* (linear, P=0.0004), drip loss (linear, P=0.0001) and cooking loss (linear, P=0.0058) in the breast. Furthermore, increasing the LFTM concentrations led to decline in protein (linear, P<0.0001), but increase in fat (linear, P<0.0001) and moisture (linear, P=0.0006) of the breast meat. The inclusion of the LFTM in the diet affected the fatty acid composition in breast and thigh meat in a dose dependent manner. Increasing the dietary levels of LFTM increased the saturated (SFA) fatty acids in the breast (linear, P=0.0012) and thigh (linear, P<0.0001) as well as the content of monounsaturated (MUFA) fatty acids in both cuts (linear, P<0.0001). This was associated with decrease in the polyunsaturated (PUFA) fatty acids in the meat of the birds fed higher levels of LFTM (linear, P<0.0001), thus producing higher atherogenic (AI) (linear, P<0.0001) and thrombogenic indices (TI) (linear, P<0.0001). The results of this study suggest that LFTM might be included in amount up to 5% in the diet of broilers without adverse effects on meat quality.